1997
DOI: 10.1136/gut.40.6.754
|View full text |Cite
|
Sign up to set email alerts
|

Pre-illness dietary factors in inflammatory bowel disease.

Abstract: Crohn's disease (CD)) and 144 controls. Odds ratios (OR) for IBD were derived for intake levels of various foods. Results-A high sucrose consumption was associated with an increased risk for IBD (OR 2 85 (p=003) against population controls and 5 3 (p=000) against clinic controls). Lactose consumption showed no effect while fructose intake was negatively associated with risk for IBD (NS). Similar trends were noted in UC and CD. A high fat intake was associated with an increased risk for UC; this was particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
221
0
13

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(245 citation statements)
references
References 27 publications
6
221
0
13
Order By: Relevance
“…An interesting ®nding however, was the signi®cantly higher intake of total carbohydrates in CD patients compared with controls. Many studies have postulated that sugar intake may be a risk factor in the development of CD (Persson et al, 1992;Tragnone et al, 1995;Thornton et al, 1979;Reif et al, 1997). It is suggested, however, that the greater consumption of sugars in CD patients may be a result rather than a cause of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting ®nding however, was the signi®cantly higher intake of total carbohydrates in CD patients compared with controls. Many studies have postulated that sugar intake may be a risk factor in the development of CD (Persson et al, 1992;Tragnone et al, 1995;Thornton et al, 1979;Reif et al, 1997). It is suggested, however, that the greater consumption of sugars in CD patients may be a result rather than a cause of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nasilenie występowania próchnicy u chorych było wyjaśniane zwiększeniem konsumpcji węglowoda-nów podczas choroby, które są jednym z głównych czynników przyczynowych próchnicy [18][19][20]. Reif et al [21] na podstawie analizy jakościowej i ilościowej oraz historii diety nowo zdiagnozowanych pacjentów stwierdzili u nich dużą konsumpcję sacharozy przed rozpoznaniem choroby Crohna. Z kolei Sundh i Emilson [15] tych samych pacjentów z chorobą Leśniowskiego-Crohna zbadali dwukrotnie w odstępie trzyletnim i wykazali większy przyrost próchnicy w porównaniu z grupą kontrolną przy braku zmian dietetycznych w tym okresie.…”
Section: Omówienieunclassified
“…An evaluation of the studies on the effects of diet and food products on disease development demonstrated that breast-milk and a diet rich in vegetables and fruit as well as vitamin C were protective against the development of UC (3)(4)(5). Food products that provoke the development of UC include cow's milk in allergic individuals, n-6 fatty acids, processed red meat, refined sugars, food with high sulfide content, fatty foods, and 'fast food' (6-9) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%